The effects of trainings applied with CoQ10 and zinc supplementation on the thyroid hormone metabolism in Soccer players - Polat, Metin; Polat, Yahya; Akbulut, Taner; Cinar, Vedat; Marangoz, Irfan (Scientific Publishers of India, 2017)
This study aims at examining the effects of zinc and CoQ10 supplementation applied with 8 w trainings on the thyroid hormone metabolism. The study was conducted on 60 voluntary male football players whose average of age is 20.60 ± 3.15 y and average of weight is 66.20 ± 4.74 kg. The participants were divided equally into 4 groups. The groups were constituted in the following way: 1st group: group which is supplied with zinc (Z), 2nd group: group which is supplied with coenzyme Q10 (Q), 3rd group: control group which does only physical exercises (C) and 4th Group: Group which is supplied with zinc and coenzyme Q10 (ZQ). At the first week of the study, TSH, T3 and T4 levels of the participants were measured from the samples which were drawn from the participants at Pre-exercise resting period (PreRP), post-exercise pre-test fatigue (PreTF), and pre-exercise post-test rested (PostTR) and post-exercise posttest fatigue (PostTF) after 8 w supplementation period. As a consequence, it was discovered that 8 w trainings led to increases in both rested and post-exercise fatigue TSH levels of only the group supplied with zinc (p<0.05). Considering T3 values, it was discovered that statistically significant differences between the PreTF values and PreTR and PostTR values of the control group and the PreTF values were found to be lower than these two measurements (p<0.05). When CoQ10 supplementation was applied with exercises, differences were observed between the PostTF and PostTR T3 values (p<0.05). As zinc and CoQ10 supplementation were given, post 8 w training T3 values decreased when compared to the pre 8 w training values (p<0.05). Regarding T4 values, it was discovered that PostTF values were lower than the PreTR values of only the group supplied with zinc. The result of this being that, the zinc and CoQ10 supplementation applied with 8 w football trainings were found to be effective on the thyroid hormone metabolism. It is believed that antioxidant supplementation may make significant contributions to the thyroid metabolism functions. © 2017 Scientific Publishers of India. All rights reserved.
Keywords: CoQ10; Soccer; T3; T4; TSH; Zinc